An improved process for the release of synthetic DNA sequences from a solid-phase capture support. (14th September 2022) - Grajkowski, Andrzej; Cawrse, Brian M.; Takahashi, Mayumi; Beaucage, Serge L.
Graphical abstract: Abstract: To facilitate the solid-phase purification of synthetic DNA sequences, a riboside phosphoramidite, carrying a 5- O -capture linker and a 2- O -silyl ether protecting group, is incorporated into a DNA sequence during its last solid-phase synthesis cycle. After deprotection and release of the DNA sequence from the synthesis support, the sequence is then covalently linked to a capture support to enable the removal of shorter unbound DNA sequences by simply washing these off the support. The solid-phase purified DNA sequence is then released from the capture support, through an innovative intramolecular cyclodeesterification of its terminal riboside ethyl phosphate triester entity and is isolated in a yield of 94% while displaying an exquisite purity of 97%.